Structural and functional studies in vitro on the p6 protein from the HIV-1 gag open reading frame - Stys, D; Blaha, I; Strop, P (Biochimica et biophysica acta, 1993)
Protein p6 from HIV-1 gag open reading frame is reported to affect both the final phase of assembly of the viral particle and the early stage of the gag polyprotein maturation in vitro. Two separate hypotheses have been proposed, on only one of these reported effects. We think that both observations may be eventually explained if p6 protein strongly inhibits the HIV-1 proteinase. Protein p6 was synthesised by solid-phase peptide synthesis. Several methods of folding the p6 protein were tested, each resulting in the random structure according to both CD and 1D proton NMR spectra. A uniformly high exposure of NH protons to the solution was confirmed by temperature-dependent NMR spectra and isotope exchange experiments. Thus the p6 protein does not have any rigid conformation in solution. A rigid structure is not formed after further cleavage by HIV-1 proteinase as neither the protein nor its fragments are cleaved by this proteinase. In addition, the p6 protein itself does not act as inhibitor of HIV-1 proteinase. This excludes a direct role of p6 protein and supports the hypothesis that p6 is involved in forming the appropriate structure of gag polyprotein precursor. The role of slowly cleaved tight gag-proteinase in the final stage of maturation may be to slow down maturation of the precursor polyproteins prior to their transport to final location in the membrane.
Keywords: DNA vazebné proteiny; otevřené čtecí rámce; Viral Proteins; sekvence aminokyselin; software; inhibitory HIV-proteasy; HIV-1; Molecular Sequence Data; Amino Acid Sequence; HIV Protease Inhibitors; magnetická rezonanční spektroskopie; molekulární sekvence - údaje; Protein Structure, Secondary; Circular Dichroism; virové proteiny; DNA-Binding Proteins; sekundární struktura proteinů; Software; Open Reading Frames; Magnetic Resonance Spectroscopy; cirkulární dichroismus